Epidemiology and Synergistic Hepatopathology of Malaria and Hepatitis C Virus Coinfection. Issue 1 (3rd August 2017) - Nasir, Idris Abdullahi; Yakubu, Sa'adatu; Mustapha, Jelili Olaide
Malaria and hepatitis C virus (HCV) infections are very common causes of human suffering with overlapping global geographic distributions. With the growing incidence of HCV infections in malaria-endemic zones and malaria in areas with exceptionally high HCV prevalence, coinfections and syndemism of both pathogens are likely to occur. However, studies of malaria and HCV coinfections are very rare despite the fact that liver-stage plasmodiasis and hepatitis C develop in hepatocytes which may synergistically interact. The fact that both pathogens share similar entry molecules or receptors in early invasive steps of hepatocytes further makes hepatopathologic investigations of coinfected hosts greatly important. This review sought to emphasize the public health significance of malaria/HCV coinfections and elucidate the mechanisms of pathogens' entrance and invasion of susceptible host to improve on existing or develop antiplasmodial drugs and hepatitis C therapeutics that can intervene at appropriate stages of pathogens' life cycles.